Capital Structure and its Determinants During the Pre and Post Period of Recession : Pecking Order vs. Trade Off Theory - De, Anupam; Banerjee, Arindam (Indian Journal of Finance, 2017)
This research study was undertaken to understand if there were any significant changes in variables influencing the capital structure decisions of BSE 500 companies in the post period of recession in comparison with the pre - period of recession. A further endeavor was made in this article to investigate if there was a shift in the financing behavior of the firms during the same period of the study. It was observed from the study that the financing behavior of the firms was explained by the pecking order theory in the pre - recession period and trade off theory during the post - recession period.